A=(2/9-7/2)×4/3+(16/9-5/12)×4/3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{4}{5}\) : (\(\dfrac{4}{5}\) .- \(\dfrac{5}{4}\)) : (\(\dfrac{16}{25}\) - \(\dfrac{1}{5}\))
= \(\dfrac{4}{5}\) : (-1) : (\(\dfrac{16}{25}\) - \(\dfrac{5}{25}\))
= -\(\dfrac{4}{5}\) : \(\dfrac{11}{25}\)
= - \(\dfrac{4}{5}\) x \(\dfrac{25}{11}\)
= - \(\dfrac{20}{11}\)
\(\dfrac{4}{5}\): (\(\dfrac{4}{5}\).-\(\dfrac{5}{4}\)) : (\(\dfrac{16}{25}\) - \(\dfrac{1}{5}\))
=\(\dfrac{4}{5}\) x - 1: (\(\dfrac{16}{25}\) - \(\dfrac{5}{25}\))
= - \(\dfrac{4}{5}\) : \(\dfrac{11}{25}\)
= - \(\dfrac{4}{5}\) x \(\dfrac{25}{11}\)
= - \(\dfrac{20}{11}\)
\(\dfrac{11}{12}\): (\(\dfrac{7}{9}\) + - \(\dfrac{1}{3}\)) - (\(\dfrac{2}{3}\) - \(\dfrac{5}{15}\))
= \(\dfrac{11}{12}\) : (\(\dfrac{7}{9}\) - \(\dfrac{3}{9}\)) - (\(\dfrac{2}{3}\) - \(\dfrac{1}{3}\))
= \(\dfrac{11}{12}\) : \(\dfrac{4}{9}\) - \(\dfrac{1}{3}\)
= \(\dfrac{11}{12}\) x \(\dfrac{9}{4}\) - \(\dfrac{1}{3}\)
= \(\dfrac{99}{48}\) - \(\dfrac{16}{48}\)
= \(\dfrac{83}{48}\)
a) 1/2 + 3/4 - (3/4 - 4 - 5)
= 1/2 + 3/4 - 3/4 + 4 + 5
= (3/4 - 3/4) + (4 + 5) + 1/2
= 0 + 9 + 1/2
= 19/2
b) [9/16 + 8/(-27)] - (19/27- 7/16 - 2)
= 9/16 - 8/27 - 19/27 + 7/16 + 2
= (9/16 + 7/16) + (-8/27 - 19/27) + 2
= 1 - 1 + 2
= 2
c) -5/8 . [4/9 + 7/(-12)]
= -5/8 . (-5/36)
= 25/288
d) 7/10 . (-3/5) + 7/10 . (-2/5) - (-3/10)
= 7/10 . (-3/5 - 2/5) + 3/10
= 7/10 . (-1) + 3/10
= -2/5
e) -3/7 . 5/9 + 4/9 . (-3/7) + 2 3/7
= -3/7 . (5/9 + 4/9) + 17/7
= -3/7 . 1 + 17/7
= 2
f) 8 2/7 - (3 4/9 + 4 2/7)
= 8 + 2/7 - 3 - 4/9 - 4 - 2/7
= (8 - 3 - 4) + (2/7 - 2/7) - 4/9
= 1 - 4/9
= 5/9
h) 3.(-1/2)² - (4/5 + 8/15) : 5/6
= 3.1/4 - 4/3 : 5/6
= 3/4 - 8/5
= -17/20
4.[-2(8:4) + 15(-3) - (-12)]
= 4.[-2.2 - 45 + 12]
= 4.[-4 - 45 + 12]
= 4.[-49 + 12]
= 4.[-37]
= - 148
3.(25 : 5 - 14 : 2) - 5.(6:2)
= 3.(5 - 7) - 5.3
= 3.(-2) - 15
= - 6 - 15
= -21
a) Ta có: \(\dfrac{-5}{7}\left(\dfrac{14}{5}-\dfrac{7}{10}\right):\left|-\dfrac{2}{3}\right|-\dfrac{3}{4}\left(\dfrac{8}{9}+\dfrac{16}{3}\right)+\dfrac{10}{3}\left(\dfrac{1}{3}+\dfrac{1}{5}\right)\)
\(=\dfrac{-5}{7}\cdot\dfrac{3}{2}\cdot\dfrac{21}{10}-\dfrac{3}{4}\cdot\dfrac{56}{3}+\dfrac{10}{3}\cdot\dfrac{8}{15}\)
\(=\dfrac{-9}{4}-14+\dfrac{16}{9}\)
\(=\dfrac{-1621}{126}\)
b) Ta có: \(\dfrac{17}{-26}\cdot\left(\dfrac{1}{6}-\dfrac{5}{3}\right):\dfrac{17}{13}-\dfrac{20}{3}\left(\dfrac{2}{5}-\dfrac{1}{4}\right)+\dfrac{2}{3}\left(\dfrac{6}{5}-\dfrac{9}{2}\right)\)
\(=\dfrac{-17}{26}\cdot\dfrac{13}{17}\cdot\dfrac{-3}{2}-\dfrac{20}{3}\cdot\dfrac{3}{20}+\dfrac{2}{3}\cdot\dfrac{-33}{10}\)
\(=\dfrac{3}{4}-1-\dfrac{11}{5}\)
\(=-\dfrac{49}{20}\)
Bài 1: Tìm \(x\)
a; \(x-2\) + 7 = 1.3.(-9)
\(x\) - 2 + 7 = 3.(-9)
\(x\) - 2 + 7 = - 27
\(x\) = - 27 - 7 + 2
\(x\) = - 34 + 2
\(x\) = - 32
Vậy \(x=-32\)
Bài 1
c; - 2\(x\) + 5 = 7
- 2\(x\) = 7 - 5
- 2\(x\) = - 2
\(x\) = -2 : (-2)
\(x\) = - 1
Vậy \(x\) = - 1
a) \(2+\dfrac{3}{4}\)
\(=\dfrac{8}{4}+\dfrac{3}{4}\)
\(=\dfrac{8+3}{4}\)
\(=\dfrac{11}{4}\)
b) \(\dfrac{1}{3}+\dfrac{3}{2}-\dfrac{7}{4}\)
\(=\dfrac{4}{12}+\dfrac{18}{12}-\dfrac{21}{12}\)
\(=\dfrac{4+18-21}{12}\)
\(=\dfrac{1}{12}\)
c) \(\dfrac{1}{6}+\dfrac{3}{8}-\dfrac{1}{4}\)
\(=\dfrac{4}{24}+\dfrac{9}{24}-\dfrac{6}{24}\)
\(=\dfrac{4+9-6}{24}\)
\(=\dfrac{7}{24}\)
d) \(\dfrac{5}{12}+\dfrac{3}{8}\times\dfrac{4}{9}\)
\(=\dfrac{5}{12}+\dfrac{3\times4}{8\times9}\)
\(=\dfrac{5}{12}+\dfrac{1}{6}\)
\(=\dfrac{5}{12}+\dfrac{2}{12}\)
\(=\dfrac{7}{12}\)
e) \(\dfrac{4}{5}-\dfrac{1}{5}\times\dfrac{7}{2}\)
\(=\dfrac{4}{5}-\dfrac{1\times7}{5\times2}\)
\(=\dfrac{4}{5}-\dfrac{7}{10}\)
\(=\dfrac{8}{10}-\dfrac{7}{10}\)
\(=\dfrac{8-7}{10}\)
\(=\dfrac{1}{10}\)
f) \(\dfrac{16}{9}-\dfrac{4}{15}:\dfrac{2}{5}\)
\(=\dfrac{16}{9}-\dfrac{4}{15}\times\dfrac{5}{2}\)
\(=\dfrac{16}{9}-\dfrac{4\times5}{15\times2}\)
\(=\dfrac{16}{9}-\dfrac{2}{3}\)
\(=\dfrac{16}{9}-\dfrac{6}{9}\)
\(=\dfrac{16-6}{9}\)
\(=\dfrac{10}{9}\)
a: =8/4+3/4=11/4
b: =4/12+18/12-21/12=1/12
c: =4/24+9/24-6/24=7/24
d: =5/12+12/72
=5/12+1/6
=5/12+2/12=7/12
e: =4/5-7/10
=8/10-7/10=1/10
f: =16/9-4/15*5/2
=16/9-20/30
=16/9-2/3
=16/9-6/9=10/9
a/ x-2+7=-27
x-2=-34
x=-32
b/ Đề bị điên ak?
c/ -2x=2
x=-1
d/ ko hỉu đề
`A=(2/9-7/2) xx 4/3 +(16/9 - 5/12) xx 4/3`
`A=4/3 xx [(2/9-7/2)+(16/9-5/12)`
`A=4/3 xx [2/9 - 7/2 + 16/9 - 5/12]`
`A=4/3 xx [(2/9+16/9)+(-7/2-5/12)]`
`A=4/3 xx [18/9 + (-42/12 - 5/12)]`
`A=4/3 xx [2 -47/12]`
`A=4/3 xx [24/12 - 47/12]`
`A=4/3 xx (-23/12)`
`A=-23/9`
Vậy `A=-23/9`
A=(2/9-7/2)×4/3+(16/9-5/12)×4/3
A=[2/9-7/2+16/9-5/12]×4/3
A=[(2/9+16/9) - (7/2+5/12)] x4/3
A=[ 2 - 47/12] x 4/3
A= (-23/12) x 4/3
A= -23/9